Loss of Acetylcholine Signaling Reduces Cell Clearance Deficiencies in Caenorhabditis elegans. - Sérgio M Pinto; Johann Almendinger; Juan Cabello; Michael O Hengartner (PLoS ONE, 2016)
The ability to eliminate undesired cells by apoptosis is a key mechanism to maintain organismal health and homeostasis. Failure to clear apoptotic cells efficiently can cause autoimmune diseases in mammals. Genetic studies in Caenorhabditis elegans have greatly helped to decipher the regulation of apoptotic cell clearance. In this study, we show that the loss of levamisole-sensitive acetylcholine receptor, but not of a typical neuronal acetylcholine receptor causes a reduction in the number of persistent cell corpses in worms suffering from an engulfment deficiency. This reduction is not caused by impaired or delayed cell death but rather by a partial restoration of the cell clearance capacity. Mutants in acetylcholine turn-over elicit a similar phenotype, implying that acetylcholine signaling is the process responsible for these observations. Surprisingly, tissue specific RNAi suggests that UNC-38, a major component of the levamisole-sensitive receptor, functions in the dying germ cell to influence engulfment efficiency. Animals with loss of acetylcholine receptor exhibit a higher fraction of cell corpses positive for the "eat-me" signal phosphatidylserine. Our results suggest that modulation by ion channels of ion flow across plasma membrane in dying cells can influence the dynamics of phosphatidylserine exposure and thus clearance efficiency.